About “Ayub’s Story” That Fascinated Franz Kafka - Kuvanova Shakhnoza Omonovna (Genius Journals, 2023)
Franz Kafka was the creator of the world’s strangest and most abstract destiny, who set the development of 20th century literature in a new direction, decided a special attitude to man and his life. The article highlights the source of “Ayub’s story” that served as the basis for writing the novel “Process”, but it is analyzed that the philosophical, literary and religious views of the text of the novel related to the stories in the divine book have not been sufficiently studied. Therefore, the article analyzes the story that inspired the writer, which source was used, and the writer's views on this matter
Keywords: Ayub’s story; Franz Kafka; supernatural puzzle